Regional reputation as the price premium: estimation of a hedonic model for the wines of Castile-La Mancha - Castillo-Valero , J. Sebastián; Villanueva , Emiliano C.; García-Cortijo, M. Carmen (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
Wine is a multi-attribute product and one of great differentiation. Consumers do not know wines’ intrinsic properties before its purchase; consumers need and look for extrinsic signals that allow them to infer those intrinsic properties. To evaluate those intrinsic wine properties, the article uses price as an extrinsic signal to express their value. The price used is a comparison between the prices suggested by the specialized guides and the ones proposed directly to the consumer at the on-line stores. With the hedonic price methodology, which relates price and attributes, the article shows the convergence between the value referenced (price) by the Spanish experts and the one paid (price) in the Spanish market, the former being independent of the interests of the economic agents and the latter not. Regional reputation is the only attribute that positively impacts the price of Castilian wine and is prioritized in the ranking of attributes.